Master Music Composition: Symphonic Poem “The Artificial (Un)intelligence” - Laithong, Thawin; Dhamabutra, Narongrit (Rangsit Music Journal, 2021)
Symphonic Poem “The Artificial (Un)intelligence” is related to computer science and artificial intelligence, which are significantly issued of our time that will soon affect humanity unavoidably. This composition is presented in the style of program music, describing the composer’s concept and imagination on artificial intelligence. The composition consists of three movements. This composition is scored for orchestra and synthesizer in order to represent the function of artificial intelligence inspired by composer’s imagination. The composer is influenced by minimalist music, by using the repetition and other techniques from contemporary music. The estimated duration of “The Artificial (Un)Intelligence” is 14 minutes.